+0  
 
0
62
2
avatar

Find h(x), with terms in order of decreasing degree, if
3x^4+2x-1+h(x)=5x^2-6x-1

 Jul 27, 2020
 #1
avatar+781 
+1

Let's take this term by term. We have 3x^4+2x-1 and 5x^2-6x-1. h(x) must have -3x^4 because all x^4 terms cancelled in the sum, 5x^2 because there was no x^2 term before so this must have been added, and -8x because 2x-8x=-6x.. So h(x) is -3x^4+5x^2-8x.

 Jul 27, 2020
 #2
avatar+27691 
+1

3x^4+2x-1+h(x)=5x^2-6x-1      subtract  3x^4 + 2x -1   from both sides

h(x)  = -3x^4 + 5x^2 - 8x

 Jul 27, 2020

40 Online Users

avatar